2015
DOI: 10.1371/journal.pone.0145302
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Toll-Like Receptor and the IL-23/IL-17 Pathways Were Associated with Susceptibility to Inflammatory Bowel Disease in a Danish Cohort

Abstract: BackgroundThe inflammatory bowel diseases (IBD), Crohn’s disease (CD) and ulcerative colitis (UC), result from the combined effects of susceptibility genes and environmental factors. Previous studies have shown that polymorphisms in the Toll-like receptor (TLR), the apoptosis, the IL-23/IL-17 and the interferon gamma (IFNG) pathways are associated with risk of both CD and UC.MethodsUsing a candidate gene approach, 21 functional single nucleotide polymorphisms (SNPs) in 15 genes were assessed in a clinical homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…Intestinal epithelial TLR5 expression could be beneficial in the neonate host as discussed above but the subsequent down‐regulation in absorptive enterocytes might help to prevent inappropriate stimulation in the adult host. Consistently, a loss‐of‐function polymorphism in TLR5 has been shown to protect whereas a gain‐of‐function was associated with an increased risk of inflammatory bowel disease in humans . Additionally, soluble factors in breast milk such as epidermal growth factor, the local cytokine milieu and regulatory molecules such as A20 may help to avoid inappropriate innate immune stimulation during the immediate postnatal period …”
Section: Postnatal Maturation Of the Neonatal Innate Immune Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…Intestinal epithelial TLR5 expression could be beneficial in the neonate host as discussed above but the subsequent down‐regulation in absorptive enterocytes might help to prevent inappropriate stimulation in the adult host. Consistently, a loss‐of‐function polymorphism in TLR5 has been shown to protect whereas a gain‐of‐function was associated with an increased risk of inflammatory bowel disease in humans . Additionally, soluble factors in breast milk such as epidermal growth factor, the local cytokine milieu and regulatory molecules such as A20 may help to avoid inappropriate innate immune stimulation during the immediate postnatal period …”
Section: Postnatal Maturation Of the Neonatal Innate Immune Systemmentioning
confidence: 98%
“…Consistently, a loss-offunction polymorphism in TLR5 has been shown to protect whereas a gain-of-function was associated with an increased risk of inflammatory bowel disease in humans. 43,44 Additionally, soluble factors in breast milk such as epidermal growth factor, the local cytokine milieu and regulatory molecules such as A20 may help to avoid inappropriate innate immune stimulation during the immediate postnatal period. 28,45,46 In addition to developmental factors, the innate immune system actively adapts to the situation after birth.…”
Section: Postnatal Maturation Of the Neonatal Innate Immune Systemmentioning
confidence: 99%
“…These diseases processes are complex and involve both environmental and genetic factors. Genetic studies have shown that polymorphisms in the Toll‐like receptor (TLR), IL‐23/IL‐17, interferon gamma (IFNG), and apoptosis pathways are associated with susceptibility to CD and UC (Bank et al, ). In the IL‐23/IL‐17 pathway, IL‐23 increases the excretion of the pro‐inflammatory cytokine IL‐17, which in turn enhances the production of pro‐inflammatory mediators such as IL‐1β, IL‐6, IL‐8, and TNF‐α (Andrews et al, ).…”
Section: Chronic Inflammation and Epigenetic Alterationsmentioning
confidence: 99%
“…The SNPs were evaluated for genotyping errors by assessing Hardy-Weinberg equilibrium. This was performed in a control group of healthy Danish blood donors 51 as HardyWeinberg equilibrium cannot be assessed in the current highly selected study group of patients with psoriasis selected for treatment with biological therapy. The control group was genotyped by the same method at the same laboratory.…”
Section: Study Populationmentioning
confidence: 99%